Fluorescence enhancement on silver nanoplates at the single- and sub-nanoparticle level. Issue 47 (16th November 2015) - Shen, Yangbin; He, Ting; Wang, Wenhui; Zhan, Yulu; Hu, Xin; Yuan, Binfang; Zhou, Xiaochun
Abstract : Super-resolution microscopy is used to image the diverse patterns of fluorescence enhancement on single triangular silver nanoplates. Abstract : The fluorescence intensity of a fluorescent molecule can be strongly enhanced when the molecule is near a metal nanoparticle. Hence, fluorescence enhancement has a lot of applications in the fields of biology and medical science. It is necessary to understand the mechanism for such an attractive effect, if we intend to develop better materials to improve the enhancement. In this paper, we directly image the diverse patterns of fluorescence enhancement on single Ag nanoplates by super-resolution microscopy. The research reveals that the edges or tips of the Ag nanoplate usually show a much higher ability of fluorescence enhancement than the mid part. The spatial distribution of fluorescence enhancement strongly depends on the size of the Ag nanoplate as well as the angle between the Ag nanoplate and the incident light. The experimental results above are essentially consistent with the simulated electric field by the theory of localized surface plasmon resonance (LSPR), but some irregularities still exist. We also find that fluorescence enhancement on small Ag nanoplates is mainly due to in-plane dipole plasmon resonance, while the enhancement on large Ag nanoplates is mainly due to in-plane quadrupole plasmon resonance. Furthermore, in-plane quadrupole resonance of large plates has a higher ability to enhance the fluorescence signal than the in-plane dipole plasmon resonance. This research provides many valuable insights into the fluorescence enhancement at the single- and sub-nanoparticle level, and will be very helpful in developing better relevant materials.